TINGKAT KEPATUHAN TERAPI PASIEN GAGAL GINJAL KRONIK YANG MENGALAMI DEPRESI - Rahman, Havizur; Arifin, Helmi; Murni, Arina Widya (Jurnal Ilmiah As-Syifaa, 2019)
Depression is known to be one of the causes of noncompliance therapy. This study aims to determine the correlation between depression with compliance of chronic renal failure patients. The method in this study is cross-sectional. Data is collected by judgment sampling. Depression level is assessed by using the Beck Depression Inventory-II (BDI- II). Compliance level is assessed by using the morisky scale. The result shows an average compliance level of chronic renal failure patients is included in high compliance category (53.03%). It is found that there is not a correlation between depression and compliance of chronic renal failure patients (p> 0.05). it is concluded that there is no correlation between depression and compliance of chronic renal failure patients.